Alpine wetland degradation reduces carbon sequestration in the Zoige Plateau, China - Yang, Ao; Kang, Xiaoming; Li, Yong; Zhang, Xiaodong; Zhang, Kerou; Kang, Enze; Yan, Zhongqing; Li, Meng; Wang, Xiaodong; Niu, Yuechuan; Yan, Liang (Frontiers in Ecology and Evolution, 2022)
Alpine wetland plays an important role in the global carbon balance but are experiencing severe degradation under climate change and human activities. With the aim to clarify the effect of alpine wetland degradation on carbon fluxes (including net ecosystem CO2 exchange, NEE; ecosystem respiration, ER; gross ecosystem productivity, GEP, and CH4 flux), we investigated 12 sites and measured carbon fluxes using the static chamber method in the Zoige alpine wetland during August 2018, including undegraded wetland (UD), lightly degraded wetland (LD), moderately degraded wetland (MD), and severely degraded wetland (SD). The results showed that carbon sink strengths differ among the Zoige wetlands with different degradation stages during the growing season. From UD to LD, the rate of carbon sequestration (mean value of NEE) increased by 25.70%; however, from LD to SD, it decreased by 81.67%. Wetland degradation significantly reduced soil water content (SWC), soil organic carbon (SOC), microbial biomass carbon (MBC), and microbial biomass nitrogen (MBN). NEE was significantly correlated with MBC and MBN, while ER was positively correlated with ST but negatively correlated with SOC (P < 0.01). Among all measured environmental factors , GEP was positively correlated with pH (P < 0.01), while CH4 flux was most closely correlated with SOC, SWC, MBC, MBN, and ST (P < 0.001), and was also affected by pH and NO3- content (P < 0.01). These results suggest that the capacity of carbon sequestration in the Zoige wetlands reduced with intensification of the degradation. This study provides a reference for sustainably managing and utilizing degraded wetlands under climate change.